Stable Cu Catalysts Supported by Two‐dimensional SiO2 with Strong Metal–Support Interaction. Issue 9 (25th January 2022) - Wang, Shenghua; Feng, Kai; Zhang, Dake; Yang, Deren; Xiao, Mengqi; Zhang, Chengcheng; He, Le; Yan, Binhang; Ozin, Geoffrey A.; Sun, Wei
Abstract: Cu‐based catalysts exhibit excellent performance in hydrogenation reactions. However, the poor stability of Cu catalysts under high temperatures has restricted their practical applications. The preparation of stable Cu catalysts supported by SiO2 with strong metal–support interaction (SMSI) has thus aroused great interest due to the high abundance, low toxicity, feasible processability, and low cost of SiO2 . The challenge in the construction of such SMSI remains to be the inertness of SiO2 . Herein, a simple and scalable method is developed to prepare 2D silica (2DSiO2 ) supported Cu catalysts with SMSI by carefully manipulating the topological exfoliation of CaSi2 with CuCl2 and thereafter calcination. The prepared Cu‐2DSiO2 catalysts with the unique encapsulated Cu nanoparticles exhibit excellent activity and long‐term stability in high‐temperature CO2 hydrogenation reactions. This feasible and low‐cost solution for stabilizing Cu catalysts might shed light on their realistic applications. Abstract : Achieving long‐term stability of Cu/SiO2 catalysts at high temperatures has been a long‐sought‐after goal for many catalytic reactions that demand low cost and high throughput. Herein, a cost‐effective and feasible route is developed to prepare a new Cu/2DSiO2 catalyst with strong metal–support interaction that exhibits ultrahigh stability at high temperatures, which is not enjoyed by the traditional impregnation method.